ä½¿ç”¨è§†å¬æ•™å¦æ³•æé«˜ç¬¬åå›½ç«‹åˆå¦ç”Ÿ å¯¹æ±‰è¯è¯æ±‡çš„æŽŒæ¡èƒ½åŠ› - Nuraini, Siti; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractVocabulary in language learning is very important, because by mastering vocabulary, students can speak according to the meaning of the dialogue. If the vocabulary learning is not adequate, it can be difficult to start a dialogue. Therefore using the audio visual method(cartoon movie)can be one of the methods to help students recognize and read vocabulary. The purpose of the research and thesis writing was to examine whether the audio visual method(cartoon movie) can improve students ability in mastering Mandarin vocabulary. The writer found that students of grade 3 of SMP N 10 feel difficult to remember the Mandarin vocabulary. The outcome shows that students learning progress is significantly improved. The results showed that the audio visual method(cartoon movie) was very good, because it was direct so it was easy for the students to understand. Apart from that, this method is very suitable in teaching Mandarin vocabulary. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: Audio Visual Methods , Mastery Ability , Vocabulary Learning